2017
DOI: 10.25258/ijpcr.v9i1.8259
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba Species in Tap Water, Egypt

Abstract: Genus Acanthamoeba causes 3 clinical syndromes amebic keratitis, granulomatous amebic encephalitis and disseminated granulomatous amebic disease (eg, sinus, skin and pulmonary infections). A total of 144 tap water samples were collected from Giza governorate, Egypt. Samples were processed for detection of Acanthamoeba species using non-nutrient agar (NNA) and were incubated at 30oC. The isolates of Acanthamoeba were identified to species level based on the morphologic criteria. Molecular characterization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…This is comparable with another study from Saudi Arabia [21] and Brazil and they reported 20% [10]. However, reports from Egypt and Poland showed a high prevalence in swimming pool water samples [1,11]. The major variation observed in different studies appears due to Acanthamoeba contamination introduced into water in soil by humans and improper maintenance and disinfection protocol in swimming pools.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is comparable with another study from Saudi Arabia [21] and Brazil and they reported 20% [10]. However, reports from Egypt and Poland showed a high prevalence in swimming pool water samples [1,11]. The major variation observed in different studies appears due to Acanthamoeba contamination introduced into water in soil by humans and improper maintenance and disinfection protocol in swimming pools.…”
Section: Discussionsupporting
confidence: 83%
“…This is very similar to the report by Winck et al [14] and they found that 9.5% from the tap water sources in Brazil. Indeed, some studies reported that higher occurrences of 26.9% in the UK [20], 29.9% in Egypt [12], 92% in drinking water samples from various sources collected from the Karachi city, Pakistan [3]. This showed that Saudi Arabia is providing good water facility throughout the Al Zulfi city.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted previously in Egypt, reported that 80%, 58.6%, 56.3%, 31.4%, 67.7% and 29.2% of water samples were positive for Acanthamoeba spp. in Beni-Suef governorate, Nile Delta governorates, Giza governorate, Cairo governorate and Faiyum governorate, respectively (Abd El Wahab et al, 2018;Al-Herrawy et al, 2017;Morsy et al, 2016;Tawfeek et al, 2016;Sakran et al, 2017;Gad and Al-Herrawy, 2016). Globally, Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted in Greater Cairo, Egypt by Al-Herrawy et al (2017), it was clear that intestinal microsporidia prevailed in 8.8% of citizens and the presence of Enterocytozoon bieneusi was higher than Encephalitozoon intestinalis in the tested human stool samples. Stool of those infected persons, in addition to feces of infected animals and birds (Gad, 2010;Al-Herrawy and Gad, 2016), might be indirectly a source of contamination of surface Nile water which is the main supply of drinking water in that province.…”
Section: Figure 1: Occurrence Of Protozoan Parasites In Raw Watermentioning
confidence: 92%